Implementasi Aplikasi Sistem Informasi Pemerintahan Daerah (SIPD) pada Dinas Perpustakaan dan Kearsipan Kabupaten Aceh Barat - Laudy Fahzura; Najamudin Najamudin (Pencerah, 2022)
The Regional Government Information System was built to facilitate the delivery of local government information to the public and was developed to produce interconnected and integrated electronic-based local government information services. This study aimed to determine the extent of the application of the Regional Government Information System application at the Library and Archives Service of West Aceh Regency. This study used qualitative methods. The data were collected with the data observation and interview, and were analyzed by using data reduction, data presentation, and drawing conclusions. The results of the study illustrated that the implementation of the Regional Development Information system application at the Library and Archives Service of West Aceh Regency was not optimal. This could be indicated that the behavior of Human Resources (HR) was not ready to face the application of the regional Government Information System application in every field due to the lack of socialization and training at the Regional Apparatus Work Unit level. Therefore, the entering regional development planning data could not be finished at the time given by Bappeda in West Aceh. The implication of this research was that the local government is obliged to provide information on regional development and regional financial information which is managed in the Regional Government Information System directly integrated with the Central Government in providing the information to the public regarding the administration of local government.